2017
DOI: 10.2527/jas2016.0874
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association of piglet responses to infection with one of two porcine reproductive and respiratory syndrome virus isolates

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a devastating disease in the swine industry. Identification of host genetic factors that enable selection for improved performance during PRRS virus (PRRSV) infection would reduce the impact of this disease on animal welfare and production efficiency. We conducted genomewide association study (GWAS) analyses of data from 13 trials of approximately 200 commercial crossbred nursery-age piglets that were experimentally infected with 1 of 2 type 2 isolates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…In addition, apart from the SSC4 region, there was little to no overlap of significant regions for host response to the NVSL versus the KS06 virus. However, genes near associated SNPs were enriched for the same gene ontology terms across PRRSV isolates, suggesting host responses to these two isolates are affected by similar biological processes (Waide et al, 2017), which is consistent with the high genetic correlation of host response to these two isolates (Hess et al, 2016).…”
Section: Selection For Host Response To Prrs By Whole-genome Predictionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, apart from the SSC4 region, there was little to no overlap of significant regions for host response to the NVSL versus the KS06 virus. However, genes near associated SNPs were enriched for the same gene ontology terms across PRRSV isolates, suggesting host responses to these two isolates are affected by similar biological processes (Waide et al, 2017), which is consistent with the high genetic correlation of host response to these two isolates (Hess et al, 2016).…”
Section: Selection For Host Response To Prrs By Whole-genome Predictionsupporting
confidence: 70%
“…A complete GWAS of host response using the PHGC trial data revealed no other genomic regions with substantial effects (Waide et al, 2017). Instead, beyond the SSC4 region, the genetic basis of host response was found to be highly polygenic, meaning that genetic differences in host response are determined by many genes across the genome, each with a relatively small effect but adding up to a substantial heritable effect.…”
Section: Selection For Host Response To Prrs By Whole-genome Predictionmentioning
confidence: 99%
“…A recent GWAS32 used single-SNP and Bayes-B methods to jointly analyze data from 13 PHGC trials on piglet responses to infection with one of two PRRSV isolates (NVSL and KS06), including the PHGC3 and PHGC5 trials that were used here. When comparing results for the NVSL isolate from the Bayes-B method performed in that GWAS with those from Boddicker et al 4.…”
Section: Discussionmentioning
confidence: 99%
“…Статус WUR как ДНК маркера подтвержден наличием у свиней с неодинаковыми генотипами по WUR различий в экспрессии (p < 0,05) гена GBP5 -члена семейства активируемых интерферонами гуанилат-связывающих белков (GBP), локализованного в непосредственной близости от WUR (14). Эффект WUR был валидирован у свиней разных пород, вакцинированных против PRRSV, инфицированных различными изолятами PRRSV, а также коинфицированных PRRSV и цирковирусом свиней типа 2b (PCV2b) (19)(20)(21).…”
unclassified